Concomitant Use of Single Antiplatelet Therapy With Edoxaban or Warfarin in Patients With Atrial Fibrillation: Analysis From the ENGAGE AF‐TIMI48 Trial. Issue 2 (23rd February 2016) - Xu, Haiyan; Ruff, Christian T.; Giugliano, Robert P.; Murphy, Sabina A.; Nordio, Francesco; Patel, Indravadan; Shi, Minggao; Mercuri, Michele; Antman, Elliott M.; Braunwald, Eugene
Abstract : Background: We studied the concomitant use of single antiplatelet therapy (SAPT) on the efficacy and safety of the anti‐Xa agent edoxaban in patients with atrial fibrillation (AF). Methods and Results: ENGAGE AF‐TIMI 48 was a randomized trial that compared 2 dose regimens of edoxaban with warfarin. We studied both the approved higher‐dose edoxaban regimen (HDER; 60 mg daily reduced by one half in patients with anticipated increased drug exposure), as well as a lower‐dose edoxaban regimen (LDER; 30 mg daily, also reduced by one half in patients with anticipated increased drug regimen). SAPT (aspirin in 92.5%) was administered at the discretion of the treating physician. Cox proportional hazard regressions stratified by SAPT at 3 months with treatment as a covariate were performed. The 4912 patients who received SAPT were more frequently male, with histories of coronary artery disease and diabetes, and had higher CHADS2 Vasc and HAS BLED scores than did the 14 997 patients not receiving SAPT. When compared to patients not receiving SAPT, those receiving SAPT had a higher incidence of major bleeding; (adjusted hazard ratio [HRadj ]=1.46; 95% CI, 1.27–1.67, P <0.001). SAPT did not alter the relative efficacy of edoxaban compared to warfarin in preventing stroke or systemic embolic events (SEEs): edoxaban versus warfarin without SAPT, hazard ratio (HRadj for HDER)=0.94; (95% CI: 0.77–1.15) with SAPT, HRadj =0.70 (95% CI: 0.50–0.98), P interaction ( P int )=0.14. (HRadj for LDER versus warfarin without SAPT=1.19 (95% CI 0.99–1.43) With SAPT, 1.03 (95% CI, 0.76–1.39) P int =0.42. Major bleeding was lower with edoxaban than warfarin both without SAPT, HRadj for HDER=0.80 (95% CI, 0.68–0.95), and with SAPT, HRadj =0.82 (95% CI, 0.65–1.03; P int =0.91). For LDER without SAPT (HRadj =0.56 [95% CI 0.46–0.67]) and with SAPT (HRadj =0.51 [95% CI 0.39–0.66]), P int =0.59. Conclusions: Patients with AF who were selected by their physicians to receive SAPT in addition to an anticoagulant had a similar risk of stroke/SEE and higher rates of bleeding than those not receiving SAPT. Edoxaban exhibited similar relative efficacy and reduced bleeding compared to warfarin, with or without concomitant SAPT. Clinical Trial Registration: URL: http://www.clinicaltrials.gov/ . Unique identifier: NCT00781391.